2023
DOI: 10.20944/preprints202302.0483.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Role of the Belgian Airborne Sniffer Measurements in the MARPOL Annex VI Enforcement Chain

Abstract: Responding to an urgent call for effective and cost-efficient enforcement of emission regulations from ocean-going vessels (OGVs) at sea, the Royal Belgian Institute of Natural Sciences, one of the 17 official partners of the Belgian coastguard structure, launched its airborne sniffer program in 2015. A custom-built sniffer sensor was installed on board of the Belgian coastguard aircraft and has been used for the in-situ measurement of SO2 and NOx in OGV exhausts, providing non-compliance alerts to port inspec… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…Given the limited number of Tier III vessels currently in operation, the NECA implementation has not yet made a signi cant impact in reducing average NO x emission factors. Furthermore, previous studies already indicated increased NO x emission factors for Tier II vessels compared to Tier I vessels 14,24,29,33,39,40 . Consequently, the outcomes of this study align closely with the conclusions drawn from other research studies.…”
Section: Discussionmentioning
confidence: 90%
“…Given the limited number of Tier III vessels currently in operation, the NECA implementation has not yet made a signi cant impact in reducing average NO x emission factors. Furthermore, previous studies already indicated increased NO x emission factors for Tier II vessels compared to Tier I vessels 14,24,29,33,39,40 . Consequently, the outcomes of this study align closely with the conclusions drawn from other research studies.…”
Section: Discussionmentioning
confidence: 90%
“…An OGV was considered to be non-compliant when it was measured with a value exceeding the yellow threshold. As non-compliance can, strictly speaking in accordance with the EU Sulfur Directive (2016/802) [3] and the European Commission Decision (2015/253) [7], only be legally proven with a positive fuel sample taken in port. All non-compliance detections at sea referred to in this evaluation are expressed as alleged non-compliance.…”
Section: Evaluation Of Non-compliancementioning
confidence: 99%
“…A mechanism was put in place to alert Belgian port inspection authorities to target those potential violations. By conducting these "remote" measurements (theoretically these types of measurements are in fact in-situ measurements), the Belgian port inspection authorities may reduce the number of mandatory port inspections by 50% [7].…”
Section: Introduction 1belgian Sniffer Programmentioning
confidence: 99%
“…Source [8] discusses management tools for enforcing sulfur oxide reduction regulations in Latvia and Lithuania, providing insights into practical implementation. The work [9] introduces a novel method using Computational Fluid Dynamics (CFD) modeling to identify fuel sulfur content violations, showcasing technological advancements, while [10] offers valuable insights into crafting international regulations to address air pollution from ships, emphasizing the need for cohesive policies.…”
Section: Introductionmentioning
confidence: 99%